The relationship between individualism and collectivism towards collaborative learning among University Technology Malaysia student / Nur Juziyana Jasmi - Jasmi, Nur Juziyana (2013)
The purpose of this article describes about the relationship of individualism and collectivism towards collaborative learning among University Technology Malaysia students. This paper was descriptive that shown how far the level of individualism and collectivism were applied in order to determine the level of individualism and collectivism towards collaborative learning. Collaborative learning involve in a process of knowledge construction through discussion, debate and argumentation that will be result in deep learning and understanding towards individualism and collectivism. Nevertheless, this paper was emphasizing only three variables which were individualism, collectivism and collaborative learning. Then, the individualism and collectivism was discussed about the different patterns of endorsement that related to individualism and collectivism on the individual level that was distributed within national contexts. This paper also focuses at students from IPT A which University Technology Malaysia (UTM) students. The data was gathered by using the questionnaire method that had answered by I 00 of students from the University Technology Malaysia (UTM). The study finds the relationship of individualism and collectivism towards collaborative learning among University Technology Malaysia (UTM) students. Then, the hypothesis was accepted where there have significant relationship collectivism towards collaborative learning among University Technology Malaysia (UTM) students. Hence, based on finding, collaborative learning was totally influenced student in learning environment.